Ana B. Dice .. - Dunrea, Olivier; Reggianini, Ernesto (Columbus, Ohio : SRA Macmillan/McGraw-Hill, 1995)
Life on the farm is never dull for Ben, who faithfully follows his big sister's advice in such things as swallowing a live minnow so he can swim like a fish or washing his face in raindrops so he will never grow old.
Keywords: Sisters -- Juvenile fiction; Farm life -- Juvenile fiction